Experimental study on the flow-induced vibrations of a circular cylinder with a rear flexibly hinged splitter plate - Muñoz-Hervás, J. C.; Lorite-Díez, M.; Ruiz-Rus, J.; Jiménez-González, J. I. (Physics of fluids (1994), 2024)
The flow around a circular cylinder is a canonical configuration that may be encountered in many engineering applications, as for instance, civil engineering, architecture, or marine structures. In particular, when bluff bodies are slender and feature low mass-damping characteristics, they may undergo flow-induced vibrations (FIVs), which may result in severe structural fatigue and damage. Here, we present an experimental study on the effect of flexibly hinged splitter plates in the FIV of a flexibly mounted circular cylinder (of diameter D) subject to an uniform cross-flow of velocity u ∞. The dynamic response and forcing of the low mass-damping system is characterized for plates of different lengths Lp and different values of the torsional stiffness of the hinge kp. Reductions of the dynamic response of more than 90% can be generally reached at the upper branch, especially when a plate of length l * = L p / D = 2 with intermediate degree of torsional stiffness is attached, which is shown to represent the best solution as it mitigates the oscillations of the system (cylinder and plate) for the whole range investigated of reduced velocity U * = u ∞ / f n D = [ 3.9 , 9.8 ], where fn is the natural frequency of oscillation. In general, the hinged plates are able to attenuate the vortex-induced vibration system response by increasing shedding frequency, until the ratio f * = f / f n > 1 is reached. At high values of U *, a general transition to galloping-like dynamics, characterized by f * < 1, occurs. The tested hinged plates modify the transition between regimes, which is associated with shifts in the phase difference between the forcing and response, combining features of the dynamics of both flexible and static rigid plates already reported in the literature. The use of hinged plates has been proven to provide with a significant attenuation of the system response and its associated drag, a feature that can be considered of practical relevance in many engineering applications. In addition, the key aspects for designing these elements as the torsional stiffness and plate length have been analyzed here.